Transient analysis of human electric shock current in frequency converter IT system based on Laplace transform - YUAN Guangzhong; LIU Haisheng; YANG Zhijia; SUN Baojin; ZHANG Wei (矿业科学学报)
In order to solve the difficulty in calculating the RMS value of human electlic shcck current caused by pulse modulated wave in case of electrocution accident in low voltage frequency converter IT power supply system of open-pit coal mine fire fighting, a transient analysis method based on Laplace transform is proposed. A transient analysis method of human elcctric shock current based on the Laplace transform is proposed to analyze the RMS value of the human electric shock current on the input side and output side of the frequency converter by establishing a piecewise linear model (PLM), and the distribution parameters on both sides of the frequency converter, the carrier frequency, the output frequency, and the load on the output side are investigated to characterize the influence of the electric shock current by constructing a MATLAB/Siumlink simulation model. The results show that the magnitude of human electric shock current is positively correlated with the capacitance distributed on each side of the frequency converter and the carrier frequency of the frequency converter under the different cases of distribution capacitance of 0.01~1.0 μF, output frequency of 30~60 Hz, and carrier frequency of 1~3 kHz, while it has little relationship with the output frequency of the frequency converter and the load connected to the output side. The simulation test results confirm the correctness of the theoretical analysis.